Designing IT Governance Approach Standard ISO 38500 for Indonesia Higher Education - Arnes Yuli Vandika; Samsul Arifin; Eka Imama Novita Sari; Debi Herlina Meilani (International Conference On Law, Business and Governance (ICon-LBG), 2013)
The use of IT to support operational activities of an organization in both small and large scale, developed into a fundamental necessity in the face of the global era. University as an educational organization working to implement IT solutions to help its street operations and serve customers (students). ISO (the International Organization for Standardization) and IEC (the International Electrotechnical Commission) form the specialized system for worldwide standardization. National bodies that are members of ISO or IEC participate in the development of International Standards through technical committees established by the respective organization to deal with particular fields of technical activity. ISO and IEC technical committees collaborate in fields of mutual interest. Other international organizations, governmental and non-governmental, in liaison with ISO and IEC, also take part in the work. In the field of information technology, ISO and IEC have established a joint technical committee, ISO/IEC JTC 1.